Lulu and the cat in the bag - McKay, Hilary (Lulu, 2013)
"When a mysterious bag is left on Lulu's doorstep, the last thing her grandmother expects to be in it is a cat--a huge, neon orange cat. But Lulu knows this cat doesn't mean any harm and in fact it needs a lovely new home"--